DETERMINAN TINGKAT DEPRESI MAHASISWA PADA MASA PANDEMI COVID-19 ( STUDI KASUS MAHASISWA UNIVERSITAS AIRLANGGA SURABAYA): Determining Of Student Depression Level In The Covid-19 Pandemic Period (Case Study Of Airlangga University Students Surabaya) - Ahmad Rido'i Yuda Prayogi; Pandu Puji Hardini; Mirah Alamiyyah; Kurnia Indah Sari; Dani Nasirul Haqi; Jayanti Dian Sari (Journal of Community Mental Health and Public Policy, 2020)
Coronavirus diesease 2019 (COVID-19) is a dangerous diesease, which spreads very easily and quickly until at this time it became a pandemic. The Work From Home (WFH) is one way to stop the spread of COVID-19 properly. The impact of WFH on a person can cause depression. This study aimed to determine the determinants of the level of depression during the COVID-19 pandemic in Airlangga University students, Surabaya. The type of observational was a cross-sectional approach. The population in the study was active students at Airlangga University, class 2016, 2017, 2018, and 2019. That the minimum research sample was 384. This study showed that the prevalence of student depression level is 48.4% with a value p-value = 0.03. There was a significant influence between age, gender, and college year on the level of depression of Universitas Airlangga students.